Pengaruh Investment Opportunity Set Dan Kebijakan Deviden Terhadap Nilai Perusahaan (Studi Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2012-2017) - Hestina Hestina (Science of Management and Students Research Journal (SMS), 2019)
This study consists of independent variables, namely market to book value of assets ratio, market to book value of equity ratio, capital expenditure book value asset, divident and the dependent variable is the dividend payout ratio. Formulation of the problem of how to influence the independent variables on the dependent variable simultaneously and partially. In this study the method used is quantitative descriptive method and the analytical tool used is a statistical analysis tool consisting of multiple linear regression models, classical assumption tests (normality, multicollinearity, heterokedacity and autocorrelation), hypothesis testing (f test and t test), and test the coefficient of determination (R2). Based on the results of the study assisted by SPSS 21 devices, the regression equation Y = 3.598 + (1.213 X1) + (0.110 X2) + (0.023) X3 + 0.628 X4 + e produces the other side simultaneously obtaining the independent variable test significantly influencing the dependent variable. Marked by Fcount> Ftable which is 37.865 > 2.76 with a significant level of 0.000 <0.05. And partially only significant company size is indicated by tcount = -10.187< ttable = 2.05954 meaning that the value of the company size is smaller than the specified level of 0.05. The conclusion obtained by the F test (Simultaneous) is that the independent variable has a significant influence on firm value. While for the t test (partial) only mktba and dividen has a significant effect on the dependent variable (dividend payout ratio).